Assessing the Impact of Crop Growth Stages and Management Practices on Soil Water Content at Different Soil Depths under Dryland Conditions - Sebetha, E. T.; Modi, A. T. (Current Research Progress in Agricultural Sciences Vol. 4, 2024)
Soil and water conservation is one of the cardinal principles of land management in rainfed areas with considerable potential for increased productivity. Soil water availability is controlled by the matric potential at which the water is held. Soil water loss through evaporation plays a role in low crop productivity and this is due to poor cropping systems and soil surface coverage. The objective of this study was to determine the effect of cropping system, crop growth stages and location on soil water content. The study was carried out at three locations in the North-West province of South Africa, which were Potchefstroom, Taung and Rustenburg during the 2011/12 and 2012/13 planting seasons. The experimental design was a factorial experiment laid out in a randomised complete block design (RCBD) with three replicates. The experiment consisted of five cropping systems, which were monocropping cowpea, monocropping maize, cowpea followed by maize in rotation, maize followed by cowpea in rotation and intercropping maize-cowpea. The three crop growth stages compared in this study were before tasselling/flowering, during tasselling/pod formation and during physiological maturity of maize and cowpea. The monthly mean temperature and rainfall data for Potchefstroom, Taung and Rustenburg for the duration of the experimental period were analysed. The soil was sampled for the 0-0.15, 0.15-0.3, 0.3-0.6 and 0.6-0.9 m depth increments and soil water content was determined using the Gravimetric method. Analysis of variance was performed using GenStat 15th edition (2012). The crop growth stage before tasselling/flowering in maize/cowpea had significantly (P < 0.05) higher water content of 10.2, 10.8, 12.5 and 13.3% at the depth of 0-0.15, 0.15-0.3, 0.3-0.6 and 0.6-0.9 m respectively. Soil collected at Rustenburg and Potchefstroom had significantly (P < 0.05) higher water content of 13.5 and 10.2; 15.9 and 10.9; 18.3 and 12.8; 18.4 and 14.5% at the depths of 0-0.15, 0.15-0.3, 0.3-0.6 and 0.6-0.9 m respectively. Monocropping cowpea plots had significantly (P < 0.05) higher water content of 12.4% than other cropping systems at the soil depth of 0.3-0.6 m. Monocropping plots of cowpea had the ability to hold soil water and this depends on the type of cowpea cultivar and canopy cover. The stage before tasselling/flowering of maize-cowpea (V10/Vn) was found to have high soil water content. Soil water content differs across locations due to different soil physical properties. In other words, soil water content is location-dependent. The production of crops such as cereals and legumes in this study is recommended to be in the area with an average clay percentage.